77 A review of left main stem percutaneous coronary intervention at a tertiary centre in the United Kingdom. (4th June 2021) - Ramakrishnan, Anenta; Cosgrove, Claudia; Briceno, Natalia; Spratt, James
Abstract : Introduction: The role of percutaneous coronary intervention (PCI) in left main stem (LMS) disease continues to evolve with advances in stent technology, adjuncts such as intracoronary imaging, calcium modification techniques and left ventricular support devices. Moreover, with changes in the demographics of the UK population and of the patient population presenting with left main coronary artery disease, the applicability of findings from historic clinical trials is uncertain. Aim: We set out to review our routine clinical practice at our tertiary PCI centre. We aimed to compare our practice to contemporary best practice guidelines and to identify a process for on-going audit and improvement. Methods: We performed a retrospective review of all procedures coded for 'Percutaneous Coronary Intervention Left Main Stem' at our centre from 1st December 2018 to 1st June 2019. Coronary angiogram reports and electronic notes for each patient were reviewed. Angiographic images and intracoronary imaging were by two operators. Results: Thirty cases were identified, for twenty-nine individual patients. The average age of patient undergoing LMS PCI was 74 years old. 24 patients were male, 5 patients were female. 28 patients had greater than two co-morbidities, including chronic kidney disease (14 patients) and type 2 diabetes mellitus (11 patients). Nearly two thirds of patients had known left ventricular systolic dysfunction (n=17). The majority of cases (n=12) were for acute coronary syndrome, including 8 for ST-elevation myocardial infarction (STEMI) and/or out of hospital cardiac arrest. The remainder were elective cases for stable angina where optimal medical therapy had failed to relieve symptoms and surgery was not deemed appropriate. Intracoronary imaging was recorded in 24 cases, the majority of which (n=23) employed intravascular ultrasound (IVUS). However, only four cases had documented minimum luminal area (MLA) or minimum stent area (MSA). Thirteen cases required calcium modification, including by cutting balloon (n= 6), intravascular lithotripsy (n=7), and rotational atherectomy (n=1).Sixteen cases had distal left main bifurcation disease, and bifurcation PCI techniques included provisional 1-stent (n=6), provisional 2-stent (n=8), Culotte (n=7) and T and small protrusion (TAP) stenting. There were four in-hospital deaths, all in patients presenting with STEMI. One patient had a cardiac cause or procedural-related cause for re-presentation to our centre before 1st December 2019 (at least 6 months post-procedure). This presentation was related to heart failure and the patient did not require revascularisation. Conclusions: The case and coronary complexity of patients undergoing left main stem PCI is very high in our centre. We found that the use of intracoronary imaging was not always well documented and available for retrospective review. In view of the high number of cases requiring calcium modification and the high number of cases that included distal left main bifurcation disease, we have taken steps to support the mandated use of intracoronary imaging in left main stem disease within the coronary catheter laboratory team, including educational training and technical support. Conflict of Interest: None